Primary gut aspergillosis in a patient with acute myeloid leukaemia: the importance of early suspicion and definitive treatment. (18th March 2014) - Li, Elizabeth; Hussein, Hayder; Todiwala, Adil; Kirby, Robert
Abstract : Aspergillus infection is a known complication in immunocompromised patients, particularly in those with impaired neutrophil function. The pathophysiology of respiratory tract infection and disseminated disease are well understood, and guidelines exist for early detection and treatment. The gut has been speculated to be the potential portal of entry for Aspergillus, though previous case series outline that this is often discovered late and results in high morbidity and mortality. Early clinical suspicion, with definitive surgical intervention and antifungal treatment with voriconazole, can significantly increase the chances of survival. In this article, the authors discuss a case of primary gut aspergillosis with secondary dissemination in a patient with acute myeloid leukaemia who developed serious sequelae.